Computational simulations and experiments on additive manufacturing of one metal to another dissimilar base metal - Lee, Sheralyn Ying (Nanyang Technological University, 2023)
This study focuses on determining the optimal process parameters for multi-material additive manufacturing (MMAM) fish-scale interface shape between two dissimilar metals: SS316L and CuZrCr by examining the mechanical properties and microstructure of the fabricated metals. SS316L and CuZrCr was fabricated using SLM process with layer thickness 50μm. The printed samples were evaluated using Vicker’s Microhardness test, tensile test, and laser microscopy. The mechanical analysis showed relationship between the Hv, ultimate tensile strength and varying laser power and scan speed. When the energy input is too low(0J/mm^3-20J/mm^3) or too high(140J/mm^3-180J/mm^3) there will be defects formed on the microstructure. The estimated optimal Hv and ultimate tensile strength was 170N/mm^2 and 370MPa respectively therefore the analysis suggested that the optimal process parameters are Laser power=275W, Patch distance=110μm, exposure time=40μm, V=360 mm/s. Computational Simulation was used to simulate the printing of the powder SS316L and CuZrCr. It is to study the interface morphology using melt pool theory and the mechanism of interlayer interface in SLM manufacturing. Melt flow characteristics are affected by the difference in melting point between SS316L and CuZrCr and the surface temperature gradient during melting. Also, recoil pressure and Marangoni force that drive the melt pool flow can impact the interface shape during melting.